Pemanfaatan Media Sosial dalam Memasarkan Produk Usaha (Studi Kasus Usaha Kue Easy Cookies Minahasa Utara) - Jemmy O.E. Rawis; Stevy P. Pangemanan (Jurnal Syntax Admiration, 2024)
This study aims to find out what social media and benefits are used by Easy Cookies Business in marketing cookie products. The use of social media for Easy Cookies cake business in marketing cake products is a survey research and analyzed descriptively to describe actual results. The research method used is the case study method. Data collection was carried out by survey method (direct observation in the field to get detailed information through interviews or in-depth interviews using questionnaires to Easy Cookies cookie business owners. The results showed that Facebook, Mesenger and whatsApp are the media used by Easy Cookies cake business to market cake products. The benefits used are as a means of promotion, cake product information and communication with consumers effectively.